Otaku : Japan's database animals - Azuma, Hiroki, 1971- (University of Minnesota Press, 2009)
"Hiroki Azuma's Otaku offers a critical, philosophical, and historical inquiry into the characteristics and consequences of this consumer subculture. For Azuma, one of Japan's leading public intellectuals, otaku culture mirrors the transformations of postwar Japanese society and the nature of human behavior in the postmodern era. A vital non-Western intervention in postmodern culture and theory, Otaku is also a perceptive account of Japanese popular culture"--Provided by publisher